The Mysterious Mount Zion Mug - Gibson, Shimon (The Biblical archaeology review, 2025)
A fragmentary stone mug from the first century CE, discovered during the Mt. Zion excavations just outside Jerusalem’s Old City walls, bears a remarkable secret: a carefully incised inscription partially written in a rare cryptic script previously known only from the Dead Sea Scrolls. Investigate this mysterious text and what it may reveal about Jewish ritual practices during the Second Temple period.